Portal Vein Dopplerflowmetry in healthy sheep according to age - Belotta, Alexandra F. [UNESP]; Santarosa, Bianca P. [UNESP]; Ferreira, Danilo O.L.; Carvalho, Sílvia M.F.; Gonçalves, Roberto C. [UNESP]; Padovani, Carlos R. [UNESP]; Mamprim, Maria J. [UNESP] (FapUNIFESP (SciELO), 2017)
Pulsed Doppler ultrasound was used to evaluate portal blood flow, portal velocity and portal congestion index in 24 healthy sheep divided into groups (lambs, yearlings and ewes), according to age. Measurements were performed at the 11th right intercostal space using ideal insonation angle and uniform insonation method. Mean values obtained in each group were compared with one-way ANOVA, followed by Tukey post-hoc test. Portal velocity and portal blood flow were statistically similar between the groups (P > 0.05). Mean portal velocity were 17.75; 17.13 and 16.75; while mean portal blood flow were 26.65; 31.04 and 24.32 for lambs, yearlings and ewes, respectively. Portal congestion index was statistically distinct between the groups and values for lambs, yearlings and ewes were 0.009; 0.058 and 0.09, respectively (P < 0.01). Statistical differences were observed in portal vein diameter, portal vein area and portal congestion index between the groups, presumably due to influence of weight and not to age.
Keywords: Doppler; Liver; Portal vein; Portal Vein Dopplerflowmetry; Sheep; Ultrasonography